Oceanside dwelling for Mrs. Clinton Walker, sheet 5, section A-A - Frank Lloyd Wight:::::::::
Section drawing which Mills traced from Frank Lloyd Wright's original design for the Walker residence, with additions contributed by Mills for his project on the residence. Includes details on cast iron columns, doors, battens and plan of fireplace.